A new viscosity semi-implicit midpoint rule for strict pseudo-contractions and (α, β)-generalized hybrid mappings. (2nd December 2021) - Song, Yanlai; Pei, Yonggang
Abstract : In this paper, we suggest and analyse a new viscosity semi-implicit midpoint iterative scheme for strict pseudo-contractions and ( α, β ) -generalized hybrid mappings in real Hilbert space. Further, some strong convergence theorems for finding a common fixed point of strict pseudo-contractions and ( α, β ) -generalized hybrid mappings are proved. And some applications are provided to quasi-variational inclusion problems. A numerical example is also given to demonstrate our results.